Stare Południe przeciwko tyranii Unii – spór o naturę Stanów Zjednoczonych w epoce „antebellum” - Tulejski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
According to the author, the roots of the American Civil War lie in the constitutional controversy that already existed during the Philadelphia convention. The dispute over the shape of the Union led to the constitutional compromise , which did not define the relationship between the federal government and the states clearly enough. The interpretation of the Constitution in the first decades of the United States and the centralization of power led to the Southern separatism, which was founded on the concept of states’ rights. Basing on it, Southern politicians derived the right to nullify the acts of federal power and ultimately the right to secede. In the article the author analyzes the views of the most prominent representatives of the South: John Taylor of Caroline, St. George Tucker, Robert Y. Hayne and John C.Calhoun, who laid the theoretical foundations of resistance to the tyranny of the Union.
Keywords: tyranny; US Constitution; American Civil War; Old South